Injury surveillance in accident and emergency departments: to sample or not to sample?. Issue 1 (March 1998) - Morrison, A; Stone, D H
Abstract : Objectives —To establish whether injury surveillance based on sampling strategies is as valid as total patient surveillance. Methods —Canadian Hospitals Injury Reporting and Prevention Program (CHIRPP) data for 1996 were retrospectively analysed using five sampling frames. Proportions for key variables were calculated for each sample, then compared with the proportions for the total population of patients. Results —Two of the five sampling frames produced statistically significant differences from the total population, which can be explained by seasonal variations. However, no significant differences were observed between the remaining three samples and the total population. Conclusions —A well planned and executed sampling strategy can generate as valid data as total patient surveillance, obviating the need for data collection on every patient presenting with an injury or poisoning. In practice, however, systematic sampling can be difficult to implement and sustain, counterbalancing the economic advantages.